Long-Term Impacts of Conditional Cash Transfers : Review of the Evidence - Molina Millán, Teresa (Published by Oxford University Press on behalf of the World Bank, 2020)
Conditional Cash Transfer (CCT) programs, started in the late 1990s in Latin America, have become the antipoverty program of choice in many developing countries in the region and beyond. This paper reviews the literature on their long-term impacts on human capital and related outcomes observed after children have reached a later stage of their life cycle, focusing on two life-cycle transitions. The first includes children exposed to CCTs in utero or during early childhood who have reached school ages. The second includes children exposed to CCTs during school ages who have reached young adulthood. Most studies find positive long-term effects on schooling, but fewer find positive impacts on cognitive skills, learning, or socio-emotional skills. Impacts on employment and earnings are mixed, possibly because former beneficiaries were often still too young. A number of studies find estimates that are not statistically different from zero, but for which it is often not possible to be confident that this is due to an actual lack of impact rather than to the methodological challenges facing all long-term evaluations. Developing further opportunities for analyses with rigorous identification strategies for the measurement of long-term impacts should be high on the research agenda. As original beneficiaries age, this should also be increasingly possible, and indeed important before concluding whether or not CCTs lead to sustainable poverty reduction.